Nurses, Archives, and the History of Canadian Health Care - McPherson, Kathryn (Archivaria, 1996)
As a new generation of scholars takes research in nursing history in some innovative directions, nursing archives and archivists face new demands and challenges. Many research collections are housed in small, private archives that face unique issues pertaining to access, privacy, and funding. Whether working with large or small archives, historians and archivists alike confront significant gaps in the primary resource base for nursing history, and must at the same time grapple with how best to define the category of nurse, past and present. RÉSUMÉ Comme une nouvelle génération de spécialistes entreprend des recherches en histoire des sciences infirmières en empruntant de nouvelles directions, les centres d'archives et les archivistes dans ce domaine font face à des demandes nouvelles et à de nouveaux défis. Plusieurs collections occupent des petits centres d'archives privés qui rencontrent des problèmes de communicabilité, de protection des renseignements personnels et de financement. Qu'ils travaillent dans de grands ou de petits dépôts d'archives, les historiens comme les archivistes rencontrent de sérieuses lacunes au niveau des sources premières dans le domaine de l'histoire des sciences infirmières et doivent en même temps définir au mieux la notion même d'infirmiers(es) passée et présente.